Three big bangs: matter-energy, life, mind (2008) - Rolston, Holmes, 1932-2025, speaker; Rollin, Bernard E., speaker (Colorado State University. Libraries, 2008)
Dr. Rolston speaks to "three big bangs" in natural history: 1. At the primordial big bang, matter-energy appears; 2. Life explodes on Earth with DNA discovering, storing, and transferring information; 3. The human genius, a massive singularity, crosses a trans-genetic threshold, generating language and making possible cumulative transmissible cultures, radically novel in kind and in scale.
Willard O. Eddy lecture given by Dr. Holmes Rolston, III, University Distinguished Professor and Professor of Philosophy Emeritus at Colorado State University, Fort Collins, Colorado on September 18, 2008. Introduction by Bernard E. Rollin.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: universe; cosmic singularity; evolution; theory of everything; cosmological constant; intellect; big bang theory